Editoral - Cláudia Gomes Silva; Yaidelin Manrique; Ricardo Santos (U.Porto Journal of Engineering, 2024)
Product Engineering is an essential component in engineering training. The jobs in the Chemical Engineering sector have been evolving from commodities production to product development, particularly in countries such as Portugal, where the scale of production is more adapted to customized or medium-sized series than mass production. So, in 2009, the Master’s in Chemical Engineering Programme at the Faculty of Engineering of the University of Porto (FEUP) started a course on Product Engineering. In 2022, a special issue in the U.Porto Journal of Engineering was published, which included a series of selected works developed within the Product Engineering course at FEUP (Silva et al. 2022). The same methodology for product development laid in four cornerstones was kept in this course: